Estrategia económica en la política bélica del gobierno Bush - Fazio, Hugo (Revista de Estudios Árabes, 2014)
Professor Hugo Fazio refers to the American new world order initiated in the early nineties, an order imposed over certain countries through free market economy, with or without their consent(by the force of arms if necessary). With its war against terrorism and “evil” nations as pretext, the U.S.A. created the National Strategic Security plan, which includes new military bases the world over. The real objective is to guaranty U.S.A. energy needs and markets. Thanks to the second Gulf War, America controls the second largest oil reserve in the world, and most reconstruction contracts in Iraq were awarded to American firms.